Perbandingan Daya Dukung Pondasi Tiang Pancang Berdasarkan Data SPT Dan Hasil Uji Pile Driving Analyzer pada Gedung Kantor Walikota Baru Mataram - Serdian Eska Cahya; Hafis Hamdani; Ahmad Zarkasi (Universitas Batanghari Jambi, 2026)
The construction of the Mataram Mayor's Office requires pile foundations with adequate bearing capacity to support the building load and improve the quality of public services. This study analyzes the bearing capacity of pile foundations based on SPT test data using several calculation methods, and compares them with the results of the PDA dynamic test. By comparing several bearing capacity calculation methods, this study aims to identify the level of accuracy and deviation of theoretical estimation results from actual conditions in the field. The research method used is quantitative analysis by utilizing Standard Penetration Test (SPT) test data as the basis for calculating the bearing capacity of pile foundations using several empirical methods, namely the O'Neil & Reese, Luciano Decourt, and Briaud et al. The results show that the bearing capacity values of pile foundations calculated based on SPT test data using various empirical methods differ from the results of the PDA dynamic test, but are still within a technically acceptable range. These differences are influenced by soil characteristics and the assumptions of each method, so that certain methods tend to show results that are closer to actual conditions in the field. Pile foundation planning relies not only on theoretical calculations based on SPT data but also combines them with PDA dynamic test results to improve the accuracy and reliability of the foundation design. Furthermore, the choice of bearing capacity calculation method must be adapted to local soil conditions to ensure more representative and safe planning results.